A review on the application of photovoltaic thermal systems for building façades. (January 2020) - Riaz, Ahmad; Liang, Ruobing; Zhou, Chao; Zhang, Jili
The hybrid photovoltaic-thermal system has shown great progress. Electrical energy is produced from PV panels while thermal energy is produced via a working fluid carried through the panels. In this paper, the vertical PV/T is introduced using working fluids such as air and liquid, which serve to control the excess temperature of the PV panels as well as to collect heat to be made available as thermal energy. Installations of PV/T systems on building façades, as well as integration with other technologies such as heat pipe and heat pump are also discussed. Current studies of such building integration technologies are also explored, including the scale of application. This study aims to provide constructive information which can be used in future development of building facades for large-scale applications, to contribute to future sustainable development. Practical application : This study helps researchers and engineers who are considering photovoltaic thermal systems for building façades to have better understanding of its effect on electrical and thermal energy – for space heating, fresh air supply and hot water supply – using an active building envelope.